International business cycle and financial intermediation - Tamás Csabafi; Max Gillman; Ruthira Naraidoo (Hungarian Academy of Sciences, Institute of Economics, 2018)
The paper extends a standard two-country international real business cycle model to include financial intermediation by banks of loans and government bonds. Taking in household deposits from home and abroad, the loans are produced by the bank in a Cobb-Douglas production approach such that a bank productivity shock can explain financial data moments. The paper contributes an explanation, for both the US relative to the Euro-area, and the US relative to China, of cross-country correlations of loan rates, deposit rates, and the loan premia. It provides a sense in which financial retrenchment resulted in the US following the 2008 bank crisis, and how the Euro-area and China reacted. The paper contributes evidence of how the Euro-area has been more financially integrated with the US, and China less financially integrated, with the Euro-area becoming more financially integrated after the 2008 crisis, and China becoming less so integrated.
Keywords: E13; E32; E44; F41; 330; International Real Business Cycles; Financial Intermediation; Credit Spread; Bank Productivity; 2008 Crisis